The First Episode of Psychosis : a Guide for Patients and Their Families - Compton, Michael T. (Oxford University Press, 2009)
The First Episode of Psychosis is the ideal book for patients experiencing the frightening and confusing initial episode of psychosis, which often occurs during late adolescence or early adulthood, and which affects nearly 3% of all people over the course of their lifetime. The book covers a range of disorders, focusing on primary psychotic disorders such as schizophrenia and schizophreniform disorder, clearly describing symptoms, early warning signs, and treatment--information that is essential for patients and families faced with the challenges posed by psychosis. The book also discusses psy.